ACHIEVING EXCELLENCE IN MATERNAL, NEONATAL AND PERINATAL SURVIVAL: EXECUTIVE SYNOPSIS OF PEARL STUDY ANNUAL REPORT 2011 - Rahman, Sajjad; Ansari, Walid El; Nimeri, Nuha; Tinay, Sarrah El; Tohid, Hiba; Yousafzai, Mohammad Tahir (Journal of Postgraduate Medical Institute, 2012)
PEARL Study (Perinatal Neonatal Outcomes Research Study in the Arabian Gulf) is Qatar's prospectiveNational Perinatal Epidemiologic Study funded by QNRF (Qatar National Research Fund - grant # QNRFNPRP-09-390-3-097). The study is a joint collaborative research project between Hamad MedicalCorporation (HMC), Doha, Qatar and the University of Gloucestershire, Gloucester, United Kingdom. Theproject aims at building a National Neonatal Perinatal Registry for Qatar called Q-Peri-Reg which will beused to quantify Maternal, Neonatal and Perinatal mortality and morbidities and their correlates. Thestudy is approved by the Research Ethics Committee (IRB) of Hamad Medical Corporation (protocol#9211/09), which is responsible for providing ethical approval to all health care research projects in theState of Qatar